Kinetics and mechanism of polysulfides and elemental sulfur formation by a reaction between hydrogen sulfide and δ-MnO2. (15th November 2021) - Avetisyan, Khoren; Zweig, Irina; Luther, George W.; Kamyshny, Alexey
Abstract: Formation rates for various products of hydrogen sulfide oxidation by δ-MnO2 were studied as a function of pH, temperature, concentration of the reactants, and ionic strength at the environmentally-relevant conditions. The main goals of this work were studying the effects of these parameters on speciation of zero-valent sulfur, including individual polysulfides and revealing the mechanism of its formation. A reaction between hydrogen sulfide and manganese dioxide is the fastest environmentally-relevant abiotic process of polysulfides formation, reactive sulfur species, which participate in complexation of metals, pyrite formation, sulfurization of organic matter and may serve as a substrate for microorganisms. In the pH range of 7.0 to 10.5, zero-valent sulfur accounted for > 55% of the sulfur in the products of hydrogen sulfide oxidation, while at pH ≥ 7.5, the formation rates of polysulfide zero-valent sulfur were higher than those of particulate zero-valent sulfur formation. Speciation of polysulfides on the initial stage of the reaction shows significant shift toward the higher polysulfides compared to their speciation calculated under assumption of thermodynamic equilibrium in both H2 S - Sn 2− - S8(aq) - α-S8 and H2 S - Sn 2− - S8(aq) - S8(coll) systems. We suggest that the shift in the speciation of polysulfide system results from the presence of a short-living highly reactive sulfur atoms, which are formed on the first stage of the reaction: two-electron transfer from hydrogen sulfide to manganese dioxide. Results of this study provide constraints on the rates of polysulfide formation at the redox interfaces of the stratified aquatic systems, and allows quantitative assessment of their role in sulfur cycling.